PENGARUH LINGKUNGAN KERJA, DISIPLIN DAN PELATIHAN TEKNIS TERHADAP KINERJA PEGAWAI TEKNIS DI DINAS ENERGI DAN SUMBER DAYA MINERAL PROVINSI SUMATERA UTARA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Panaitan, Ferry; Pasaribu, Johnson; Bangun, Janpianta (Jurnal Manajemen dan Bisnis, 2022)
The purpose of this study was to analyze and determine the effect of the work environment, discipline and technical training on the performance of technical employees at the Department of Energy and Mineral Resources of North Sumatra Province with job satisfaction as an intervening variable. The research method in this study used descriptive analysis methods and verification analysis. The population in this study were all employees working at the Department of Energy and Mineral Resources of North Sumatra Province, amounting to 89 people. Of the 89 respondents who were sent a list of questions through the Whatapps application in the form of google form, only 70 respondents filled out the complete list of questions. The analysis technique used is multiple linear regression. The results showed that: (1) Partially the variables of work environment, work discipline, training and job satisfaction had a positive and significant effect on the performance of the employees of the Department of Energy and Mineral Resources of North Sumatra Province; (2) Work environment and work discipline have no significant effect on performance through job satisfaction of employees of the Department of Energy and Mineral Resources of North Sumatra Province, and (3) Simultaneously the variables of work environment, work discipline, training and job satisfaction have a positive and significant effect on performance of employees of the Department of Energy and Mineral Resources of North Sumatra Province